Love Forgiveness and Subjective Well-Being in Chinese College Students: The Mediating Role of Interpersonal Relationships - Cheng, Tianyi; Lin, Qiyi; Fu, Hong (Frontiers in Psychology, 2021)
Love forgiveness is categorized as forgiveness in a specific relationship, which is the tendency of individuals to forgive the objects of their interpersonal relationships. We investigated 831 undergraduate students in China with a love forgiveness questionnaire, a subjective well-being questionnaire and an interpersonal relationship comprehensive diagnostic, including demographic variables. Students of different genders and grades showed significant differences across the three questionnaires. There were significant correlations between love forgiveness, interpersonal relationships, and subjective well-being of Chinese college students. Interpersonal relationships played an intermediary role between love forgiveness and subjective well-being of Chinese college students. Specifically, whereas Chinese college students’ love forgiveness could directly promote the improvement of subjective well-being, love forgiveness could also indirectly improve subjective well-being through interpersonal relationships. The mediating effect of interpersonal relationships between love forgiveness and subjective well-being accounted for 40.25% of the total effect. This provides a new way of thinking for psychological counselors to approach the intimate relationship problems of college students.